A case report: Glycopyrrolate for treatment of exercise-induced hyperhidrosis. (3rd August 2017) - Negaard, Matthew; Anthony, Christopher; Bonthius, Daniel; Jepson, Matthew; Marcussen, Britt; Pelzer, Daniel; Peterson, Andrew
Objective: Hyperhidrosis can cause dehydration and exercise intolerance. There are several case reports of extremely high sweat rates in athletes. We present as case report of a 17-year-old male with the highest sweat rate recorded in the literature (5.8 L/h). Our goal was to determine if glycopyrrolate, an anticholinergic medication with primarily anti-muscarinic effects that is known to decrease sweat production, would reduce the sweat rate of our subject in a controlled exercise setting. Methods: Our patient and a control subject were subjected to an exercise protocol consisting of running on a treadmill (5.4–6.7 mile/h at 1° of incline) in a warm climate-controlled chamber after receiving 0, 2, or 4 mg of glycopyrrolate. Core temperature, heart rate, rater of perceived exertion, and sweat rate were monitored in both subjects. Results: Glycopyrrolate dose was not significantly correlated with decreased sweat rate and maximal core temperature. However, the clinical effect of reducing the sweat rate was very strong. The improvement of the subject's sweat rate allowed him to successfully return to sport. Conclusion: Our findings suggest that low-dose glycopyrrolate may be a safe and effective method of controlling exertional hyperhidrosis.